A tipi ve B tipi kişilik özellikleri ile iş stresi ve işe yabancılaşma arasındaki ilişkinin belirlenmesi üzerine bir araştırma - Kirt, Burcu (Bartın Üniversitesi, Lisansüstü Eğitim Enstitüsü, 2022)
Geçmişten günümüze değişen dünya koşullarında, bireyin önemi her geçen gün artmaktadır. Bireyi oluşturan en temel özellikler kişilik üzerinde toplanmış olup, bu özellikler ile birey hakkında bir fikir yürütebilmek mümkün olmaya başlamıştır. Araştırmaların birçoğunda kişiliklerine göre bireyleri kategorize edilebilmek kurumlar açısından önem taşımaktadır. Kurumlar değişen dünyaya ayak uydurmak ve doğru çalışanı seçmek için kişiliğe ihtiyaç duyabilmektedir. Bunların dışında kurumda çalışmakta olan bireylerin doğru işlere yönlendirilebilmesi içinde kişilik önem arz etmektedir. Çalışanların uygun işlerde daha verimli ve mutlu çalışması, kuruma uzun vadede fayda sağlayabilmektedir. Bunların dışında işten ayrılma, işe devamsızlık, performans düşüklüğü, personel devir hızında azalma, iş stresi ve yabancılaşma gibi olumsuz durumların önüne geçmek içinde önemlidir. Bu araştırma özel sektörde çalışan beyaz yakalı çalışanların A ve B tipi kişilik özelliklerine göre iş stresi ve işe yabancılaşmanın arasındaki ilişkiyi ölçmek amacıyla yapılmıştır. Araştırma Eylül 2021 yılı ile Aralık 2021 yılı arasında Türkiye'de özel sektörde çalışan beyaz yakalı 242 kişi üzerinde uygulanmıştır. Araştırmada verileri toplanmak için nicel araştırma yöntemi olan anket yöntemi kullanılmıştır. Ankette toplam 31 ifade bulunmaktadır. Ankette demografik özelliklerle ilgili ifadelerin yanında üç farklı ölçekte kullanılmıştır. Bunlar "A Tipi ve B Tipi Kişilik Tipolojileri Envanteri", "İş Stresi Ölçeği" ve "İşe Yabancılaşma Ölçeği" olarak sıralanabilir. Toplanan veriler SPSS programında analiz edilmiştir. Ölçeklerin güvenilirliğini ölçmek için güvenilirlik testi yapılmıştır. A ve B tipi kişilik özelliklerinin iş stresi ve işe yabancılaşma arasındaki ilişkiyi analiz etmek için Pearson Korelasyon testi uygulanmıştır. Demografik özelliklerin A ve B tipi ile iş stresi ve işe yabancılaşma durumuna göre farklılık gösterip göstermediğini ölçmek için T-testi ve Anova testi uygulanmıştır. Analiz sonuçlarına göre özel sektörde çalışan beyaz yakalı çalışanların, A ve B tipi kişilik özelliklerine göre iş stresi ve işe yabancılaşma arasında anlamlı pozitif yönde bir ilişki olduğu ortaya çıkmıştır. Araştırmaya katılan kişilerden, A tipi kişilik özellikleri gösteren katılımcıların B tipi kişilik özellikleri gösteren katılımcılarında daha fazla olduğu ortaya çıkmıştır. Ayrıca A tipi kişilik özellikleri gösteren çalışanların, iş stresi ve işe yabancılaşma durumlarını yaşama olasılığının daha fazla olduğu sonucuna varılmıştır. Araştırma sonuçları kurumsal açıdan değerlendirildiğinde; A tipi kişilik özelliklere sahip bireylerin sayıca fazla olması, kurumlar için olumsuz etkenler olan iş stresi ve işe yabancılaşmanın ortaya çıkma ihtimalini arttırmaktadır. Buna bağlı olarak kurumların verimliliği azalırken, maddi kayıpları artabilmektedir. Kurumların gelecekleri açısından, iş stresi ve işe yabancılaşmanın önüne geçmesinde kişilik kavramının irdelenmesi önemli görülmektedir.

In the changing world conditions from past to present, the importance of the individual is increasing day by day. The most basic features that make up the individual are collected on personality. With these features, it has become possible to form an opinion about the person. It is important for institutions to be able to categorize individuals according to their personalities in most of the studies.Institutions may need personality in order to keep up with the changing world and to choose the right employee.Apart from these, personality is important in directing the individuals working in the institution to the right jobs. Employees working more efficiently and happily in suitable jobs can benefit the organization in the long run. Apart from these, it is important to prevent negative situations such as leaving the job, absenteeism, poor performance, decrease in personnel turnover, job stress and alienation. This research was conducted to measure the relationship between job stress and work alienation according to A and B type personality characteristics of white-collar employees working in the private sector. The research was conducted on 242 white-collar employees working in the private sector in Turkey between September 2021 and December 2021. The survey method, which is a quantitative research method, was used to collect data in the study. There are a total of 31 statements in the questionnaire. In the questionnaire, three different scales were used in addition to statements about demographic characteristics. These can be listed as "Type A and Type B Personality Typologies Inventory", "Work Stress Scale" and "Work Alienation Scale". The collected data were analyzed in the SPSS program. A reliability test was conducted to measure the reliability of the scales. Pearson Correlation test was applied to analyze the relationship between type A and B personality traits, job stress and work alienation. T-test and Anova test were applied to measure whether demographic characteristics differ according to A and B types, job stress and work alienation. According to the results of the analysis, it has been revealed that there is a significant positive relationship between job stress and work alienation according to A and B type personality characteristics of white-collar employees working in the private sector. Among the people participating in the research, it was revealed that the participants showing type A personality characteristics were more than the ones showing type B personality characteristics. In addition, it was concluded that employees with type A personality characteristics are more likely to experience work stress and work alienation. When the research results are evaluated from an institutional point of view; The high number of individuals with type A personality characteristics increases the probability of experiencing job stress and job alienation, which are negative factors for institutions. As a result, while the efficiency of the institutions decreases, their financial losses may increase. In terms of the future of institutions, the concept of personality should be examined in order to prevent work stress and alienation from work.
A study on determining the relationship between work stress and work alienation with type A and type B personality
Keywords: A tipi ve B tipi kişilik; A tipi kişilik; B tipi kişilik; Kişilik; İş stresi; Stres; İşe yabancılaşma; Yabancılaşma; Type A and type B personality; Type A personality; B type personality; Personality; Work stress; Stress; Work alienation; Alienation